2006
DOI: 10.1175/mwr3093.1
|View full text |Cite
|
Sign up to set email alerts
|

3DVAR and Cloud Analysis with WSR-88D Level-II Data for the Prediction of the Fort Worth, Texas, Tornadic Thunderstorms. Part II: Impact of Radial Velocity Analysis via 3DVAR

Abstract: In this two-part paper, the impact of level-II Weather Surveillance Radar-1988 Doppler (WSR-88D) radar reflectivity and radial velocity data on the prediction of a cluster of tornadic thunderstorms in the Advanced Regional Prediction System (ARPS) model is studied. Radar reflectivity data are used primarily in a cloud analysis procedure that retrieves the amount of hydrometeors and adjusts in-cloud temperature, moisture, and cloud fields, while radial velocity data are analyzed through a three-dimensional vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
117
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 150 publications
(121 citation statements)
references
References 13 publications
4
117
0
Order By: Relevance
“…The ARPS 3DVAR system, described in Gao et al (2002Gao et al ( , 2004 and Hu et al (2006b), is used for this purpose. The ARPS 3DVAR system is capable of analyzing radar radial velocity data along with conventional observations.…”
Section: Introductionmentioning
confidence: 99%
“…The ARPS 3DVAR system, described in Gao et al (2002Gao et al ( , 2004 and Hu et al (2006b), is used for this purpose. The ARPS 3DVAR system is capable of analyzing radar radial velocity data along with conventional observations.…”
Section: Introductionmentioning
confidence: 99%
“…The case studied is the tornadic supercell in Oklahoma on May 8, 2003. This case was selected mainly because it was previously investigated and analyzed using the ARPS 3DVAR and cloud analysis (Hu 2005), which can provide a base line for comparisons. In the multiscale approach, EnKF analysis was performed using both 3 km and 1.5 km (1 km for some experiments) horizontal resolutions.…”
Section: Work Completedmentioning
confidence: 99%
“…Some regional models and non-hydrostatic models were built with the 3D-VAR system used for radar data assimilation (Gao et al 1999;Lindskog et al 2004;Hu and Xue 2006;Montmerle and Faccani 2009). Xiao et al (2005) developed a radar data assimilation method for MM5 and demonstrated that the method of radar wind data assimilation is useful for 6-h rainfall forecasts on a front.…”
Section: Introductionmentioning
confidence: 99%